Reconstruction of the heel defect with in-step island flap. A report of four cases. - Kwan, M.K.; Merican, A.M.; Ahmad, T.S. (Malaysian Medical Association, 2005)

(untitled)
Soft tissue loss of the heel is difficult to treat as it may cause significant morbidity particularly recurrent ulceration and subsequent chronic osteomyelitis. Reconstruction of such defect with local flap can provide good result. We report our experience in treating four patients with heel defect using the in-step island flap. The flap, which is based on the medial plantar neurovascular pedicle, provides a sensate durable tissue required for weight-bearing and normal gait.